Effects of superplasticizers on carbonation resistance of concrete. (1st April 2016) - Shi, Chen; He, Ting-shu; Zhang, Ge; Wang, Xi; Hu, Yanyan
Highlights: The effects of superplasticizers on concrete carbonation were researched. The effects of superplasticizers on carbonation of hydration products were researched. The effects of superplasticizers on concrete pore structure were investigated. The effects of superplasticizers on morphology of hydration products were investigated. The bonding state was researched by measuring the bone energy of calcium and oxygen. Abstract: The effects of polycarboxylic acid (PC), naphthalene sulfonate (NS), and aliphatic (AH) superplasticizers on the carbonation of concrete were investigated. These three kinds of superplasticizers can improve anti-carbonation performance of concrete, and their order according to magnitude of effect are as follows PC > AH > NS. The mechanism behind this phenomenon was investigated using mercury intrusion porosimetry of the concrete, thermogravimetric analysis, X-ray diffraction, scanning electron microcopy, and X-ray photoelectron spectrometry of synthetic hydrated products. The effects of superplasticizers on carbonation resistance are associated not only with pore structure but also with the morphology of hydrated products.